Analisis Teori Tujuan Hukum dan Maqaṣid Al-Syariah tentang Rekonstruksi Perjudian Online Sebagai Kejahatan Luar Biasa - Nurul Fadhilah; A Nuzul; Hamzah (Jurnal Hukum Lex Generalis, 2026)
The advancement of information technology has significantly increased the prevalence of online gambling, which not only causes economic, social, and moral harm but also raises complex legal issues, particularly related to its transnational nature, anonymity of perpetrators, and the limitations of conventional law enforcement mechanisms. The main problem addressed in this study is the inadequacy of the current legal framework in classifying online gambling as a systemic and organized crime. This study aims to analyze the reconstruction of online gambling as an extraordinary crime through the perspectives of legal purpose theory and maqāṣid al-syarī’ah. This research employs normative legal methods with statutory and conceptual approaches. The findings indicate that although online gambling has been regulated under the Criminal Code and the ITE Law, law enforcement remains ineffective due to the technological and crossborder characteristics of the crime. From the perspective of legal purpose theory, online gambling contradicts the principles of justice, utility, and legal certainty. Meanwhile, from the maqāṣid al-syarī’ah perspective, it undermines the protection of religion, life, intellect, lineage, and property. The legal implications of this reconstruction highlight the necessity of strengthening criminal policy by recognizing online gambling as an extraordinary crime, thereby enabling the application of special legal instruments such as the follow the money approach, extended jurisdiction, asset forfeiture, and enhanced international cooperation. This reconstruction is expected to improve the effectiveness of law enforcement and provide stronger protection for public interests.